Structural And Semantic Aspects of Lexemic Units Expressing National Value in English and Uzbek Languages (Eurasian Research Bulletin, 2021)
This article discusses that the study of values is one of the current areas in linguistics that requires in-depth analysis and research. In addition, the structure of concepts representing national values in English and Uzbek has been studied in several groups.